Pengaruh Celebrity Endorser, Shopping Orientation, Online Trust, dan Prior Online Purchase Experience Terhadap Minat Beli Konsumen Toko Online Elevenia di DKI Jakarta - Deasi Arindani; Riris Loisa (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Currently based on data from APJII the number of internet users in Indonesia reaches 143.26 million or around 54.68% and the number of e-commerce transactions reaches Rp 85 trillion in 2017, so this is a potential development of e-commerce in Indonesia. But according to data from Google Temasek research, one of the e-commerce Elevenia has been downgraded from I-4 quarter in 2017. PT XL Axiata sold Elevenia’s shares and was bought by Salim Group, then their made a new strategy to increase the number of purchases. In this research, there are 4 variables that can influence buying intention : Celebrity Endorser, Shopping Orientation, Online Trust, and Prior Online Purchase Experience. This research aims to determine the effect of these four variables on Buying Intention. The method used is a quantitative method with the type of research is descriptive. Sampling method used is purposive non-probability sampling with 105 respondents. The analysis technique used is multiple linear regression analysis. This research found that celebrity endorsers, shopping orientations, online trusts, and prior online purchase experience have positive and significant influence simultaneously towards buying intention by 59%, and the rest 41% is influenced by other variables not examined in this research.